Porous carbon felt / metal alloy composite electrode, preparation method thereof and application of porous carbon felt / metal alloy composite electrode in off-field electro-catalysis
By preparing porous carbon felt/metal alloy composite electrodes in an off-field electrocatalytic electrochemical cell, the problems of SO2 emissions and hydrogen resource losses in hydrogen sulfide treatment are solved, and the current density is improved and the stability and efficiency of the electrode are improved.
Patent Information
- Application Number
- CN202411803808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has problems of SO2 emissions and hydrogen resource loss in hydrogen sulfide treatment, and the metal components on the surface of the electrode are unevenly distributed, which affects the contact and current density of the electron-mediated pair.
Using porous carbon felt/metal alloy composite electrodes, the conductivity of the electrodes and the electron-mediated pair's electron exchange density are improved by depositing metal alloys in the off-field electrocatalytic electrochemical cell, and uniform dispersion of metal alloys is achieved through the current density gradient increase strategy.
The current density is increased by about 20%, eliminates the electrode hydrogen production reaction, improves the battery cathode efficiency to 99%, and significantly improves the electrode stability and cycling performance.
Smart Images

Figure CN119859819A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a porous carbon felt / metal alloy composite electrode and a preparation method thereof and application in off-site electrocatalysis, belonging to the technical field of resource utilization of harmful gases and large-scale hydrogen production from new energy sources. Background Art
[0002] Hydrogen sulfide is a harmful gas that mainly comes from petroleum refining, coal chemical industry and natural gas extraction industry. Hydrogen sulfide causes serious harm to the climate environment and human health, and must be removed in time after extraction. At present, the commonly used methods for treating hydrogen sulfide include the LO-CAT complex iron process and the Clause high-temperature oxidation method. Among them, the Clause process treats H2S on a large scale and is often used to eliminate H2S in large gas fields. The product is sulfur, but there is a large amount of SO2 emissions in the tail gas, which causes great harm to the environment and human health; in addition, all the H in H2S is discharged in the form of H2O, and hydrogen resources are greatly lost. In 2023, my country will use the Claus process to treat 7.7 billion standard cubic meters of hydrogen sulfide. If the hydrogen is recovered, the hydrogen sulfide treatment unit can be built into a hydrogen production capacity increase platform.
[0003] The patent with publication number CN111232921A discloses a method and device for producing hydrogen and sulfur by decomposing hydrogen sulfide assisted by a flow battery. This technology is a disruptive technology originally developed in my country. Under mild reaction conditions, it realizes the decomposition of H2S to produce H2 and sulfur, while reducing the floor space and investment cost, which is of great strategic significance. This technology uses two electron-mediated pairs to obtain oxidation and reduction potentials at the anode and cathode of the electrochemical cell, respectively. The electron-mediated pair that obtains the oxidation potential oxidizes hydrogen sulfide to generate sulfur and protons in a spatially separated reactor, and the electron-mediated pair that obtains the reduction potential reduces protons to generate hydrogen in another spatially separated reactor. Subsequently, the two electron-mediated pairs are regenerated at the anode and cathode of the electrochemical cell, respectively, and the protons penetrate the ion exchange membrane from the anode side to the cathode side to complete the entire cycle.
[0004] The applicant's previous research found that based on quantitative analysis, the rates of hydrogen evolution reaction and hydrogen sulfide oxidation reaction are 1.5 to 10 times the regeneration rate of electron-mediated pairs. Therefore, the key to increasing the production capacity of the above disruptive technology is to increase the current density of electron-mediated pair regeneration. Increasing the current density of the battery can achieve faster electron-mediated pair regeneration with the same electrochemical cell, increase the hydrogen sulfide processing capacity, and also reduce the footprint and area of the electrochemical system, improve its environmental adaptability and system mobility. The electron-mediated pair undergoes an electron exchange reaction on the surface of the porous carbon felt of the electrode. Analysis shows that the regeneration rate of the anode electron-mediated pair is 8 to 10 times that of the cathode electron-mediated pair, so increasing the intrinsic electron exchange density of the cathode electron-mediated pair on the porous carbon felt surface is the key. Based on the principle of off-field electrocatalysis, it can be seen that the cathode is always in a reduced state, and the porous carbon felt modified with heteroatoms such as O and N will be gradually hydrogenated to cause structural damage. Therefore, adding a conductive metal that inhibits hydrogen production is a feasible method to increase the electron exchange rate of the cathode electron-mediated pair. In addition, the cathode electron-mediated pair needs to produce hydrogen on the catalyst surface, so the added components cannot be dissolved in the acidic solution to avoid deactivation of the subsequent hydrogen evolution catalyst and shutdown of the reaction system. This is completely different from the solution to increase the current density of the electron-mediated pair in the traditional energy storage flow battery, because it involves reduction (charging) and oxidation (discharging) processes on either electrode side, and the modified components need to maintain chemical and structural stability in both processes. Even if the modified components dissolve and lose, it will only cause a decrease in energy storage power and will not cause the reaction system to stop operating.
[0005] Electrodeposition strategy is a common method for preparing porous carbon felt and metal composite electrodes, which is easy to scale up. However, due to the high solute concentration at the inlet and the gradient distribution of the current on the electrode surface, the deposited metal components are unevenly distributed, which cannot maximize the contact between the metal components and the electron-mediated pairs, and is not conducive to the improvement of the electron exchange current density. Summary of the invention
[0006] In order to solve the aforementioned technical problems, this application proposes a technical solution for preparing a porous carbon felt / metal alloy composite electrode. The highly active electrode modified with a metal alloy is used in an electrochemical cell for off-site electrocatalytic decomposition of hydrogen sulfide, which can not only improve the conductivity of the electrode and the electron exchange density of the electron-mediated pairs, but also show excellent surface stability. More importantly, no electrode hydrogen production reaction caused by the metal alloy was observed. Therefore, the innovation of this patent includes two aspects: the composite electrode preparation method and the strategy for increasing the current density.
[0007] This application adopts the following technical solutions:
[0008] According to the first aspect of the present application, a method for preparing a porous carbon felt / metal alloy composite electrode is provided, characterized in that it comprises the following steps:
[0009] Assembling the porous carbon felt into an electrochemical cell of a flow battery as a cathode electrode, adding an acidic metal salt solution into the cathode electrolyte of the electrochemical cell, and depositing metal under constant current charging conditions of a step current density to obtain the porous carbon felt / metal alloy composite electrode;
[0010] The acidic metal salt solution contains at least one soluble salt of a metal.
[0011] The electrochemical cell of the flow battery is selected from the electrochemical cell of the off-site electrocatalytic battery system, that is, the off-site electrocatalytic electrochemical cell. The off-site electrocatalytic electrochemical cell is a battery system in the electrocatalytic reaction device in the off-site electrocatalytic reaction method in the patent with publication number CN117364107A, and the electrocatalytic reaction device specifically includes:
[0012] A battery system for providing an electrolyte having redox properties;
[0013] A reaction system, which is used to provide a reaction space for the electrolyte delivered by the battery system and the reactants in the reaction system to undergo a redox reaction;
[0014] A separation system, which is used to separate the reaction product from the electrolyte after the redox reaction;
[0015] The liquid outlet of the battery system is in communication with the inlet of the reaction system;
[0016] The outlet of the reaction system is connected to the inlet of the separation system;
[0017] The electrolyte outlet of the separation system is communicated with the liquid inlet of the battery system, and the separation system has a product outlet.
[0018] The battery system comprises a liquid flow battery, which includes an anode electrolytic cell and a cathode electrolytic cell, wherein the anode and the cathode are independently selected from at least one of a carbon rod, a carbon felt, a titanium mesh and a copper mesh.
[0019] Optionally, the metal salt is selected from at least one soluble salt of a metal hydrochloride compound, a sulfuric acid compound, a phosphoric acid compound, and a nitric acid compound.
[0020] Optionally, the concentration of the acidic metal salt solution is 0.001 g / mL to 1.0 g / mL, and the acid concentration is 0.01 mol / L to 3 mol / L.
[0021] Optionally, the metal salt comprises a bismuth salt and a copper salt and / or a silver salt.
[0022] Optionally, the bismuth salt is selected from at least one of bismuth chloride, bismuth oxychloride and bismuth sulfate.
[0023] Optionally, the copper salt is selected from at least one of copper chloride, copper nitrate, copper hydrochloride and copper acetate.
[0024] Optionally, the silver salt is selected from silver nitrate.
[0025] Optionally, the step current density condition includes: the current density is from 0.1 mA / cm 2 Step increase to 50mA / cm 2 The current density step size of each step is 1~10mA / cm 2 The holding time of each step current density is 1 to 20 minutes.
[0026] Optionally, the step current density condition includes: the current density is from 0.1 mA / cm 2 Step increase to 20mA / cm 2 The current density step size of each step is 1~10mA / cm 2 The holding time of each step current density is 1 to 20 minutes.
[0027] Optionally, the charging cut-off voltage of the constant current charging is 1.5-1.6V.
[0028] Optionally, the porous carbon felt is selected from one of porous graphite carbon felt and porous graphite fiber carbon felt.
[0029] Optionally, the step further comprises washing and oxidizing the porous carbon felt before assembling the porous carbon felt into the off-site electrocatalytic electrochemical cell;
[0030] The oxidation treatment conditions include: being carried out in air, the oxidation temperature is 320-420° C., and the oxidation time is 1-120 min.
[0031] Optionally, the oxidation temperature is 360° C. to 380° C., and the oxidation time is 30 to 90 minutes.
[0032] According to another aspect of the present application, a porous carbon felt / metal alloy composite electrode obtained by the above preparation method is provided, wherein the metal alloy is deposited on the surface of the porous carbon felt;
[0033] The content of metal bismuth deposited on the surface of the porous carbon felt is 0.01-13 mg / cm 2 ;
[0034] The content of metal copper or silver deposited on the surface of porous carbon felt is 0.01~5.0mg / cm 2 .
[0035] Optionally, the content of metal bismuth deposited on the surface of the porous carbon felt is 1.0-1.6 mg / cm 2 ;
[0036] The content of metal copper or silver deposited on the surface of porous carbon felt is 0.1-0.5 mg / cm 2 .
[0037] According to another aspect of the present application, there is also provided a porous carbon felt / metal alloy composite electrode obtained by the above preparation method or the use of the above porous carbon felt / metal alloy composite electrode as a cathode in off-site electrocatalysis.
[0038] Optionally, the application includes using the porous carbon felt / metal alloy composite electrode as a cathode in off-site electrocatalytic decomposition of hydrogen sulfide to produce hydrogen and sulfur.
[0039] Optionally, the anolyte in the electrochemical cell of the off-site electrocatalytic device is 0.01 to 2 mol / L Fe 2+ The solution has a concentration of preferably 0.5 to 1 mol / L, and an acid concentration of 0.5 to 5 mol / L, preferably 2 to 3 mol / L, and more preferably 3 mol / L.
[0040] Optionally, the anode electrolyte contains at least one of hydrochloric acid, sulfuric acid and phosphoric acid.
[0041] Optionally, the cathode electrolyte in the electrochemical cell of the off-site electrocatalytic device is 0.01 to 2 mol / L V 3+ , silicotungstic acid, Cr 2+ 、Eu 2+ The concentration of at least one of the solutions is preferably 0.5 to 1 mol / L, and the acid concentration is 0.5 to 5 mol / L, preferably 2 to 3 mol / L, and more preferably 3 mol / L.
[0042] Optionally, the cathode electrolyte contains at least one of hydrochloric acid, sulfuric acid and phosphoric acid.
[0043] The electrochemical performance of the porous carbon felt / metal alloy composite electrode was tested in constant voltage mode.
[0044] The beneficial effects of this application include:
[0045] The preparation method of the porous carbon felt / metal alloy composite electrode provided in the present application is a strategy to increase the current density of the off-site electrochemical cell. The metal alloy prepared by the current density gradient increase strategy is uniformly dispersed on the surface of the porous graphite fiber carbon felt. Tests have found that single metal bismuth is easy to lose, and single metal copper or silver has obvious hydrogen production activity (accounting for about 25% of the total electricity). The presence of bismuth-copper or bismuth-silver alloys inhibits metal loss and eliminates the hydrogen production activity of the electrode. The current density is increased by about 20% under constant voltage, and the energy efficiency reaches 99%. The preparation method of the high-activity metal alloy composite electrode provided in the present application is simple and easy to control, and has excellent electrochemical activity and cycle stability. It can be applied on a large scale to off-site electrocatalytic hydrogen sulfide decomposition to produce hydrogen and sulfur technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a scanning electron microscope photo of porous graphite fiber carbon felt.
[0047] Figure 2 This is a scanning electron microscope photograph of the bismuth-copper alloy composite porous graphite fiber carbon felt labeled 1 in Table 1.
[0048] Figure 3 This is the electrochemical test stability performance of the bismuth-copper alloy labeled 1 in Table 1.
[0049] Figure 4 This is a scanning electron microscope photograph of the bismuth-copper alloy composite porous graphite fiber carbon felt in Comparative Example 2. DETAILED DESCRIPTION
[0050] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0051] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0052] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0053] The off-site electrocatalytic electrochemical cell involved in the present application is a device previously developed by the applicant, and refers to the electrocatalytic reaction device in the off-site electrocatalytic reaction method in the patent with publication number CN117364107A.
[0054] According to one embodiment of the present application, the preparation of a porous carbon felt / metal alloy composite electrode includes:
[0055] (1) preparing an acidic metal salt solution of a certain concentration; cleaning the porous carbon felt material, drying it, and then placing it in air for oxidation treatment;
[0056] (2) assembling the porous carbon felt into an off-site electrocatalytic electrochemical cell, adding an acidic metal salt solution into the cathode electrolyte, and depositing the metal using a current density gradient increase strategy to prepare a composite electrode;
[0057] (3) After the metal composite electrode obtained in step (2) is cleaned, an electrochemical activity test is directly performed.
[0058] In step (1), the metal salt concentration is 0.001 g / mL to 1.0 g / mL, the acid concentration is 0.01 mol / L to 3 mol / L, and the soluble metal salt is selected from one or a mixture of two or more of hydrochloric acid compounds, sulfuric acid compounds, phosphoric acid compounds, and nitric acid compounds; the metal salt is selected from at least one, preferably a salt solution of two different metals, and more preferably a binary combination of bismuth salt and copper salt or silver salt;
[0059] In step (1), the porous carbon felt is preferably porous graphite carbon felt, more preferably porous graphite fiber carbon felt; the air oxidation treatment,;
[0060] In step (2), the off-site electrocatalytic electrochemical cell includes a liquid storage tank, a pump and an electrochemical cell. A polybenzimidazole PBI membrane is used, and the anolyte is Fe 2+ solution, the concentration is 0.01 to 1 mol / L, preferably 0.05 to 0.1 mol / L, the acid concentration is 0.5 to 1 mol / L, preferably hydrochloric acid or sulfuric acid; the acid concentration of the cathode electrolyte is 0.01 to 1 mol / L, preferably 0.5 to 0.1 mol / L, preferably hydrochloric acid;
[0061] In step (2), the acidic metal salt solution is a binary combination of bismuth salt and copper salt or silver salt, and the content of metal bismuth deposited on the surface of the carbon felt is 0.01-13 mg / cm 2 , preferably 0.1 to 1.6 mg / cm 2 ; The content of metal copper or silver is 0.01~5.0mg / cm 2 , preferably 0.1 to 0.5 mg / cm 2 The metal bismuth salt is one of bismuth chloride, bismuth oxychloride and bismuth sulfate, preferably bismuth oxychloride; the metal copper salt is one or a combination of copper chloride, copper nitrate, copper hydrochloride and copper acetate, preferably copper chloride; the metal silver salt is silver nitrate. In special cases, a ternary combination of bismuth salt, copper salt and silver salt can be used, but a binary combination of bismuth salt and copper salt or bismuth salt and silver salt is preferred.
[0062] In step (2), the current density gradient increase strategy is to use constant current charging, and the current density is from 0.1 mA / cm 2 The gradient was increased to 50 mA / cm 2 The preferred current density range is 0.1 mA / cm 2Up to 20mA / cm 2 ; Each step is about 5mA / cm 2 , maintained for 10 minutes, the charge cut-off voltage is 1.4 to 2.0 volts, preferably 1.5 to 1.6 volts, and more preferably 1.5 volts.
[0063] In step (3), the test conditions for electrochemical activity are: the anolyte is 0.01-2 mol / L Fe 2+ The concentration of the solution is preferably 0.5 to 1 mol / L, the acid concentration is 0.5 to 5 mol / L, preferably 2 to 3 mol / L, more preferably 3 mol / L, preferably hydrochloric acid, sulfuric acid, phosphoric acid, etc., more preferably sulfuric acid; the cathode electrolyte is 0.01 to 2 mol / L V 3+ , silicotungstic acid, Cr 2+ 、Eu 2+ At least one solution of V 3+ The concentration is preferably 0.5-1 mol / L, the acid concentration is 0.5-5 mol / L, preferably 2-3 mol / L, more preferably 3 mol / L, preferably hydrochloric acid, sulfuric acid, phosphoric acid, etc., more preferably sulfuric acid; the electrochemical performance is tested in constant voltage mode.
[0064] Example 1 Preparation process of bismuth-copper alloy composite porous graphite fiber carbon felt
[0065] (1) The porous graphite fiber carbon felt was cleaned and oxidized at 360°C for 60 minutes in an air atmosphere. The scanning electron microscope photograph of the porous graphite fiber carbon felt is as follows: Figure 1 As shown;
[0066] (2) The porous graphite fiber carbon felt was assembled into an off-site electrocatalytic electrochemical cell, including a liquid storage tank, a pump, and an electrochemical cell. A polybenzimidazole PBI membrane was used, and the area of the porous graphite fiber carbon felt was 4 cm 2 , the anolyte is 0.1 mol / L Fe 2+ solution, the acid concentration is 1 mol / L; the cathode electrolyte is hydrochloric acid solution, the concentration is 1 mol / L, and the amount of bismuth metal added is 1.6 mg / cm 2 The corresponding bismuth oxychloride, the amount of copper metal added is 0.5mg / cm 2 The corresponding copper chloride.
[0067] (3) Constant current charging with a current density of 1 mA / cm 2 Stay for 10 minutes at 5 mA / cm 2 Stay for 10 minutes at 10mA / cm 2 Stay for 10 minutes at 15mA / cm 2 Stay for 10 minutes at 20mA / cm 2After 10 minutes of stay, the charging cut-off voltage was 1.5 volts, and a bismuth-copper alloy composite porous graphite fiber carbon felt was obtained, which was labeled as 1.6Bi0.5Cu / CF (CF is the abbreviation of carbon felt, the same below). The scanning electron microscope photo is shown in FIG. Figure 2 shown.
[0068] (4) By controlling the concentration of bismuth salt and copper salt in step (2), the molar ratio and content of deposited Bi and Cu are adjusted. The preparation conditions and composition of the porous graphite fiber carbon felt composited with bismuth-copper alloy are shown in Table 1, numbers 1 to 4.
[0069] Example 2 Preparation process of bismuth-silver alloy composite porous graphite fiber carbon felt
[0070] The preparation method and process are the same as those in Example 1, except that copper chloride is replaced by silver nitrate and the amount of silver metal added is 0.5 mg / cm 2 The corresponding silver nitrate, the bismuth-silver alloy composite porous graphite fiber carbon felt obtained, is marked as 1.6Bi0.5Ag / CF; by controlling the concentration of bismuth salt and silver salt to adjust the deposited Bi, Ag molar ratio and content, the preparation conditions and composition of bismuth-silver alloy composite porous graphite fiber carbon felt are shown in Table 1, numbers 5 to 8.
[0071] Test Example 1 Evaluation of electrochemical performance of metal alloy composite porous graphite fiber carbon felt
[0072] After the deposition electrolyte in the above embodiment was cleaned, the electrochemical performance was directly evaluated under the following evaluation conditions: the concentration of the anolyte was 0.5 mol / L Fe 2+ solution, sulfuric acid concentration is 3 mol / L; catholyte concentration is 0.5 mol / L 3+ The concentration of sulfuric acid was 3 mol / L. The electrochemical performance of the metal alloy composite electrode was tested using a constant voltage of 1.1 V. 2+ Oxidation to generate Fe 3+ , V occurs at the cathode 3+ Restored to V 2+ The current density at 3 minutes of operation was used for electrochemical activity comparison. Because metal modification will produce hydrogen at the cathode, reducing the efficiency of the electrochemical cell, the anode and cathode cell efficiency was calculated, and the calculation formula is: Fe 3+ or V 2+ The amount of charge contained / the amount of charge consumed by the electrochemical cell × 100%. The corresponding relationship between the sample number and the electrochemical performance is shown in Table 1. For comparison, we conducted an electrochemical activity test of a blank porous graphite fiber carbon felt, see Table 1 No. 9. The electrochemical performance of No. 1 in Table 1 after 3 cycles is shown in Figure 3 shown.
[0073] Comparative Example 1
[0074] The preparation process of bismuth or copper alloy composite porous graphite fiber carbon felt is the same as that in Example 1, except that bismuth oxychloride or copper chloride is added separately to deposit bismuth metal or copper metal. The composition and electrochemical properties of the synthesized bismuth or copper composite porous graphite fiber carbon felt are shown in Table 1, numbers 10 and 11.
[0075] Comparative Example 2
[0076] The preparation process of bismuth-copper alloy composite porous graphite fiber carbon felt is the same as that of Example 1, except that constant current charging is adopted, and the current density is fixed at 20 mA / cm 2 After 50 minutes of stay, the charging cut-off voltage was 1.5 volts. The composition and electrochemical properties of the synthesized bismuth-copper alloy composite porous graphite fiber carbon felt are shown in Table 1, No. 12. The scanning electron microscope photo of No. 12 in Table 1 is shown in Figure 4 shown.
[0077] In summary, the electrochemical activity of porous graphite fiber carbon felt composited with bismuth-copper or bismuth-silver alloy is significantly improved. Comparing No. 1 with No. 9, it can be seen that the current density is increased by about 20%, and more importantly, the battery cathode efficiency is increased to 99%. For a single bismuth-deposited electrode, the electrochemical activity is increased by 13%, and the battery cathode efficiency is increased to 97%. For a single copper-deposited electrode, the electrochemical activity is increased by about 30%, but the battery cathode efficiency is only 75%, indicating that hydrogen evolution on the electrode surface is very serious, which is an undesirable result. Bismuth-copper alloy not only improves the current density and battery cathode efficiency, but also the cycle stability at the surface. The results of bismuth-silver alloy are similar to those of bismuth-copper. In addition, when the bismuth-copper alloy is directly deposited at a constant current, the obtained sample No. 12 has a current density increase of only about 9% and a cathode efficiency of 88%. Compared with No. 1, it can be seen that the current density gradient increase strategy has excellent practical effects.
[0078] Table 1 Comparison table of metal alloy composite porous graphite fiber carbon felt sample numbers, preparation conditions and electrochemical activity
[0079]
[0080] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a porous carbon felt / metal alloy composite electrode, characterized in that: The steps include: Assembling the porous carbon felt into an electrochemical cell of a flow battery as a cathode electrode, adding an acidic metal salt solution into the cathode electrolyte of the electrochemical cell, and depositing metal under constant current charging conditions of a step current density to obtain the porous carbon felt / metal alloy composite electrode; The acidic metal salt solution contains at least one soluble salt of a metal.
2. The preparation method according to claim 1, characterized in that: The electrochemical cells of the flow battery are selected from electrochemical cells of an off-site electrocatalytic battery system.
3. The preparation method according to claim 1, characterized in that: The metal salt is at least one soluble salt selected from the group consisting of hydrochloric acid compounds, sulfuric acid compounds, phosphoric acid compounds, and nitric acid compounds of metals; Preferably, the concentration of the acidic metal salt solution is 0.001 g / mL to 1.0 g / mL, and the acid concentration is 0.01 mol / L to 3 mol / L.
4. The preparation method according to claim 1, characterized in that: The metal salts include bismuth salts and copper salts and / or silver salts; Preferably, the bismuth salt is selected from at least one of bismuth chloride, bismuth oxychloride and bismuth sulfate; Preferably, the copper salt is selected from at least one of copper chloride, copper nitrate, copper hydrochloride and copper acetate; Preferably, the silver salt is selected from silver nitrate.
5. The preparation method according to claim 1, characterized in that: The step current density conditions include: the current density is from 0.1 mA / cm 2 Step increase to 50mA / cm 2 The current density step size of each step is 1~10mA / cm 2 The holding time of each step current density is 1 to 20 minutes.
6. The preparation method according to claim 1, characterized in that: The charging cut-off voltage of constant current charging is 1.5~1.6V.
7. The preparation method according to claim 1, characterized in that: The porous carbon felt is selected from one of porous graphite carbon felt and porous graphite fiber carbon felt.
8. The preparation method according to claim 1, characterized in that: The step also includes washing and oxidizing the porous carbon felt before assembling it into the off-site electrocatalytic electrochemical cell; The oxidation treatment conditions include: being carried out in air, the oxidation temperature is 320-420° C., and the oxidation time is 1-120 min.
9. The porous carbon felt / metal alloy composite electrode obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The metal alloy is deposited on the surface of the porous carbon felt; The content of metal bismuth deposited on the surface of the porous carbon felt is 0.01-13 mg / cm 2 ; The content of metal copper or silver deposited on the surface of porous carbon felt is 0.01~5.0mg / cm 2 .
10. Use of the porous carbon felt / metal alloy composite electrode obtained by the preparation method according to any one of claims 1 to 8 or the porous carbon felt / metal alloy composite electrode according to claim 9 as a cathode in off-site electrocatalysis; Preferably, the application includes the use of the porous carbon felt / metal alloy composite electrode as a cathode in the off-site electrocatalytic decomposition of hydrogen sulfide to produce hydrogen and sulfur.
Citation Information
Patent Citations
Method and device for preparing hydrogen and sulfur by decomposing hydrogen sulfide assisted by flow battery
CN111232921A
Offsite electro-catalysis reaction method and reaction system
CN117364107A